A comparative study of psychosocial development in children who receive cochlear implants. (1st November 2013) - Warner-Czyz, Andrea D; Loy, Betty; Roland, Peter S; Tobey, Emily A
<x xml:space="preserve">Abstract</x> Objectives This study assessed self-reported quality of life of children with a cochlear implant (CI), comparing results with two published reports from the past decade. Methods Participants included 33 pediatric CI recipients with a mean age of 10.12 years (SD = 3.59), mean implantation age of 1.36 years (SD = 0.46), and mean CI experience of 6.23 years (SD = 1.75). Children in all three studies completed a self-report quality-of-life questionnaire that included seven benefit and six problem items, rated on a 5-point Likert scale. Results Outcomes revealed agreement across studies in overall benefit and problem ratings. Environmental awareness and frustration reduction were the most and least positively rated outcomes, respectively. Items contributing to overall ratings differed across studies. Current CI recipients rated speech production, making new friends, and understanding speech more positively and taking extra care of the device more negatively than previous generations of pediatric CI users. Discussion Overall, benefits outweigh problems of the device, according to children using CI. Differences in issues motivating self-report ratings reflect changes in CI candidacy, technology, and social participation over the past decade. These findings emphasize the need for clinicians to address not only communication needs, but also quality-of-life issues to optimize outcomes in children using CI.